Be [2.0] turning your business into an enduring great company - Collins, James C. (James Charles), 1958-; Lazier, William C. (New York : Portfolio/Penguin, 2020)
"What's the roadmap to create a company that not only survives its infancy but thrives, changing the world for decades to come? Nine years before the publication of his epochal bestseller Good to Great, Jim Collins and his mentor, Bill Lazier, answered this question in their bestselling book, Beyond Entrepreneurship. Beyond Entrepreneurship left a definitive mark on the business community, influencing the young pioneers who were, at that time, creating the technology revolution that was birthing in Silicon Valley. Decades later, successive generations of entrepreneurs still turn to the strategies outlined in Beyond Entrepreneurship to answer the most pressing business questions. BE 2.0 is a new and improved version of the book that Jim Collins and Bill Lazier wrote years ago. In BE 2.0, Jim Collins honors his mentor, Bill Lazier, who passed away in 2005, and reexamines the original text of Beyond Entrepreneurship with his 2020 perspective. The book includes the original text of Beyond Entrepreneurship, as well as four new chapters and fifteen new essays. BE 2.0 pulls together the key concepts across Collins' thirty years of research into one integrated framework called The Map. The result is a singular reading experience, which presents a unified vision of company creation that will fascinate not only Jim's millions of dedicated readers worldwide, but also introduce a new generation to his remarkable work" --Amazon.
Previous edition: published as Beyond entrepreneurship by James C. Collins and William C. Lazier by Prentice Hall Press, 1992.
Includes bibliographical references and index.
Keywords: Small business -- Management; Organizational effectiveness; Success in business